China’s 21st Century Geopolitics and Geo-economics: An Evidence from the Western Balkans - Nevena Šekarić Stojanović (Međunarodni Problemi)
This article advocates the thesis that the People’s Republic of China, in accordance with a strong geopolitical strategy, is using geo-economics tools in the context of reshaping global powers’ influence in diverse parts of the world. One of these spatial dimensions of Chinese emerging domination refers to the Western Balkans, primarily through the economic presence of China in this region. To address this issue first will be considered concepts of geopolitics and geo-economics, followed by highlighting China’s presence in the Western Balkans region and flourishing infrastructure projects in the domain of transport and energy. The research is conducted by relying on the existing databases on China’s economic involvement in different economy sectors worldwide, mainly from China Global Investment Tracker (CGIT) and AidData’s Global Chinese Official Finance Dataset for the WB countries in the period 2013-2018. Special attention is given to China’s benefits in terms of realizing those projects, even though the Western Balkans countries’ market is not attractive per se. Finally, some concluding remarks have been made in terms of the potentials of China’s strategy to reconsider political and security dynamics in the Western Balkans.